Circulatory Levels of RANKL, OPG, and Oxidative Stress Markers in Postmenopausal Women With Normal or Low Bone Mineral Density. Issue 14 (April 2019) - Azizieh, Fawaz Y; Shehab, Diaa; Jarallah, Khaled Al; Gupta, Renu; Raghupathy, Raj
Introduction: Receptor activator of nuclear factor κB ligand (RANKL), osteoprotegerin (OPG), and oxidative stress markers are suggested to contribute to bone loss in osteoporosis that occurs in menopause. However, the association between these markers and bone mineral density (BMD) is controversial. The aim of this study was to measure circulatory levels of these parameters in postmenopausal women with normal or low BMD. Methods: The study population included 71 postmenopausal women, of whom 25 had normal BMD, 31 had osteopenia, and 15 had osteoporosis. Serum levels of RANKL, OPG, and 5 oxidative stress markers (catalase, peroxiredoxin 2 [PRX2], superoxide dismutase 1 [SOD1], superoxide dismutase 2 [SOD2], and thioredoxin [TRx1]) were measured using the Multiplex system. Results: As compared with subjects having normal BMD, subjects with low BMD had significantly lower median serum levels of OPG, catalase, SOD2, and PRX2 ( P  = .004, .031, .044, and .041 respectively). Although levels of RANKL were not different between the 2 groups, the RANKL/OPG ratio was higher in women with low BMD ( P  = .027). Conclusions: These data provide insights into the possible roles of OPG, RANKL, and oxidative stress in the pathogenesis of postmenopausal osteoporosis. However, the lack of association between these markers and BMD indicates that osteoporosis is complex and multivariate.